Numerical analysis of tribological characteristics for textured piston ring-liners in mixed lubrication with a non-circular cylinder bore - Bahrom, Mohd Zaki; Manshoor, Bukhari; Zaman, Izzuddin; Didane, Djamal Hissein; Ng, Wei Hang; Sayed Abdelaal, Muhammed Abdelfattah; Nizam Ibrahim, Mohd Nizam (FAZ Publishing, 2022)
Piston ring packs are commonly found in the engine. It is a necessity for an engine to run smoothly. The function of the piston rings is to control the lubricant and prevent leakage. The interface of the cylinder bore with the piston rings will cause a tribology behavior. Laser Surface Texturing (LST) on the piston ring surface had shown positive results in previous studies. In this study, we are considering the surface texturing of the piston rings in a distorted bore. Moreover, the texturing detail on the piston ring surface is also considered by modifying the dimple size or the micro-groove on the surface. 3D modeling software, SOLIDWORKS is used to model the piston rings and a finite element method software called COMSOL Multiphysics is used to perform multiple simulations to obtain the result. The result shows that the texturing of the piston ring surface improves the tribology performance during the engine cycle. Meanwhile, for the surface texturing details, the large lateral aspect ratio gives a negative effect.